1975
DOI: 10.1017/s0022112075001231
|View full text |Cite
|
Sign up to set email alerts
|

Viscous effects on the position of cavitation separation from smooth bodies

Abstract: 779Flow visualization by the schlieren technique in the neighbourhood of a fully developed cavity on two axisymmetric headforms has shown the existence of laminar boundary-layer separation upstream of cavitation separation, and the distance between the two separations to be strongly dependent on Reynolds number. Based on present results, a semi-empirical method is developed to predict the position of cavitation separation on a smooth body. The method applies only in the Reynolds-number range when the cavitatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1
4

Year Published

1982
1982
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 10 publications
5
45
1
4
Order By: Relevance
“…Viscous effects are predominant in the detachment of cavitating flow near the leading edge as observed by Arakeri & Acosta [14] and confirmed by Franc & Michel [72] in the case of hydrofoils. They showed that a well-developed cavity always detaches downstream of laminar separation of the boundary layer.…”
Section: Role Of Viscositysupporting
confidence: 53%
“…Viscous effects are predominant in the detachment of cavitating flow near the leading edge as observed by Arakeri & Acosta [14] and confirmed by Franc & Michel [72] in the case of hydrofoils. They showed that a well-developed cavity always detaches downstream of laminar separation of the boundary layer.…”
Section: Role Of Viscositysupporting
confidence: 53%
“…The cavitation type triggered through this mechanism could be a foil cavitation such as the one studied by Arakeri [82] and commended by Brennen in [59] ). This gives a span-wise wave length of boundary-layer streaks as l* % 0.479  10 23 m and an estimated spanwise wavelength of GSB as l à GSB % 9:58 mm: Again, this value is roughly equivalent to the observed averaged cavitation streak spacing l à streak % 6:5 mm: Note that the three-dimensional effect disturbed the streak-forming process on both ends of the wing span.…”
Section: Boundary-layer Streak Breakdown Triggering Cavitation Inceptionmentioning
confidence: 99%
“…Heureusement dans ce domaine des progrès substantiels ont été faits ces dernières années [16] sur la base des études effectuées auparavant par ARAKERI [17]. Il semble aujourd'hui établi que la cavité est toujours .…”
Section: Prévision Du Point De Détachementunclassified